Molecular Prevalence and Genetic Diversity Based on Msp1a Gene of Anaplasma ovis in Goats from Turkiye - Ulucesme, Mehmet Can; Ozubek, Sezayi; Aktas, Munir (Mdpi, 2023)
Anaplasma ovis is a tick-borne obligated intraerythrocytic bacterium that infects domestic sheep, goats, and wild ruminants. Recently, several studies have been carried out using 16S rRNA and msp4 genes to identify the genetic diversity of A. ovis. Instead of these genes, which are known to be highly stable among heterologous strains, Msp1a, which is accepted as a stable molecular marker to classify A. marginale strains, was used in A. ovis genetic diversity studies. The genetic diversity of A. ovis strains according to the Msp1a gene has not been extensively reported. Therefore, the purpose of this study was to examine the genetic diversity of A. ovis in goats specifically using analysis of the Msp1a gene. Blood samples were taken from the vena jugularis to the EDTA tubes from 293 randomly selected goats (apparently healthy) in the Antalya and Mersin provinces of Mediterranean region of Turkiye. The Msp1a gene of A. ovis was amplified in all DNA samples through the use of PCR, using a specific set of primers named AoMsp1aF and AoMsp1aR. Among the amplified products, well-defined bands with different band sizes were subjected to sequence analysis. The obtained sequence data were converted into amino acid sequences using an online bioinformatics program and the tandem regions were examined. The Msp1a gene of A. ovis was amplified in 46.1% (135 out of 293) of the goats. Through tandem analysis, five distinct tandems (Ao8, Ao18, Tr15-16-17) were identified, and it was found that three of these tandems (Tr15-16-17) were previously unknown and were therefore defined as new tandems. The study also involved examination of ticks from goats. It was observed that the goats in the area were infested with several tick species, including Rhipicephalus bursa (888/1091, 81.4%), R. turanicus (96/1091, 8.8%), Dermacentor raskemensis (92/1091, 8.4%), Hyalomma marginatum (9/1091, 0.8%), and R. sanguineus s.l. (6/1091, 0.5%). This study provides important data for understanding the genetic diversity and evolution of A. ovis based on tandem repeats in the Msp1a protein.
Keywords: Anaplasma ovis; genetic diversity; goat; MSP1a; tandem repeats